STRATEGI PEMASARA DIGITAL DI DAA TARIK WISATA PANTAI PANDAWA, KABUPATEN BADUNG (Jurnal Destinasi Pariwisata, 2026)
Pandawa Beach is located in Kutuh Village, Badung Regency, Bali. It features gentle waves, pristine white sand, and stunning limestone cliffs. The main challenge lies in the low optimization of digital marketing, evident from Pandawa Beach's website not appearing in top search results, a lack of marketing expertise, and the absence of a dedicated marketing division. This research aims to analyze the existing marketing conditions at Pandawa Beach tourist attraction and to examine the digital marketing strategies implemented to maximize Pandawa Beach's promotional potential. Data was collected through observation, interviews, documentation, and literature review. The informant selection technique used was purposive sampling. Data was analyzed using a descriptive qualitative method with a Strength, Weakness, Opportunities, and Threats (SWOT) approach. The research findings indicate that Pandawa Beach implements a marketing mix strategy encompassing Product, Price, Place, Promotion, People, Process, and Physical Evidence (7P), as well as Segmentation, Targeting, and Positioning (STP). Its flagship products include natural beauty and the Kecak Dance, offered at affordable prices, with a strategic location, adequate access, and both direct and indirect ticket distribution. A clear organizational structure, systematic services, and aesthetic facilities support tourist comfort. Segmentation includes local, domestic, and international tourists, with an inclusive target market and positioning that highlights a blend of nature and culture in a safe and comfortable environment. Digital marketing optimization remains a challenge, particularly concerning information updates and SEO/SEM implementation. SWOT analysis reveals strengths in nature and culture, weaknesses in basic facilities and digital promotion, opportunities from niche trends and technology, and threats from competition and environmental damage. Recommended strategies include developing cultural and environmental tourism packages, implementing sustainable tourism practices, improving toilet infrastructure, optimizing digital promotion, and strengthening marketing human resources to maximize Pandawa Beach's potential and enhance its competitiveness in Bali and globally.